PEMIKIRAN TOKOH DALAM MEMUNCULKAN METAFORA PADA NOVEL SHIKISAI WO MOTANAI TSUKURU TAZAKI KARYA HARUKI MURAKAMI - Aulia, Noni; Hermandra, Hermandra; Isnaini, Zuli Laili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study discusses character’s thoughts on bring up metaphors on Haruki Murakami’s novel entitled Shikisai wo Motanai Tsukuru Tazaki. This study has two objectives. The first one is to identify the categorization of metaphors using Lakoff and Johnson (1980) theory, the second one is to analyse the meanings of metaphors using Knowles and Moon (2006) theory as guidelines. This study is a qualitative descriptive research using Haruki Murakami’s novel entitled Shikisai wo Motanai Tsukuru Tazaki as the primary data. This study finds all categories of metaphors which are 3 structural metaphors, 2 orientational metaphors, and 16 ontology metaphors. From 19 data there are 21 metaphors, and its meanings are related to depression, disappointment, despair, emptiness, sadness.Keywords : Metaphor, novel, haruki murakami, shikisai wo motanai tsukuru tazaki